ANALISIS KESULITAN SISWA DALAM MEMECAHKAN SOAL FISIKA PADA MATERI LISTRIK STATIS DI SMP NEGERI 1 TUMPAAN DI ERA COVID-19 - Egha Savitri Dali; Treesje Katrina Londa; Alfrits Komansilan (Charm Sains: Jurnal Pendidikan Fisika, 2021)
This study aims to describe students 'difficulties in solving physical problems on static electricity and to describe the factors that cause students' difficulties. This research uses descriptive qualitative method. The subjects of this study were class IXB SMP Negeri 1 Tumpaan. The data collection techniques in this study used test questions, interviews, and documentation. The data analysis technique in this study used the Miles and Huberman models, including data reduction, data testing, and inference. The results showed that the average percentage of difficulty students had in solving physical problems with static electricity material according to Polya's Problem Solving Levels: (1) Problem phase understanding was 76.66%. The reason for this is that the students forget and do not understand the meaning of the questions. (2) The planning phase for problem solving is 78.66%. The reason is that students don't know which equation to use. (3) Phase of implementation of problem-solving planning of 84.66%. The reason for this is that students don't know which equation to use. This results in the students having difficulty in the implementation phase of the plan and less able to do calculations. (4) The review phase is 90%. The reason is that the students are not thorough and do not double-check their answers.